2013
DOI: 10.5009/gnl.2013.7.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Newly Developed Endoscopic Ultrasound with Zone Sonography Technology for Diagnosis of Pancreatic Diseases

Abstract: Background/AimsTo confirm the feasibility of using newly developed endoscopic ultrasound (EUS) with Zone sonography™ technology (ZST; Fujifilm Corp.).MethodsSeventy-five patients with pancreatic disorders were enrolled: 45 with intraductal papillary mucinous neoplasm; 15 with ductal carcinoma; five with neuroendocrine tumors; three with serous cystic neoplasms; and seven with simple cysts. The endoscopes used were EG-530UR2 and EG-530UT2 (Fujifilm Corp.). Two items were evaluated: visualization depth among fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In another study, Hirooka et al reported no different SS provided by automatic adjustment of SS according to pancreatic cystic lesions and solid lesions. 27 It may be more advantageous to use other imaging modalities to differentiate between solid and cystic pancreatic lesions before performing SS.…”
Section: F I G U R Ementioning
confidence: 99%
“…In another study, Hirooka et al reported no different SS provided by automatic adjustment of SS according to pancreatic cystic lesions and solid lesions. 27 It may be more advantageous to use other imaging modalities to differentiate between solid and cystic pancreatic lesions before performing SS.…”
Section: F I G U R Ementioning
confidence: 99%
“…Technologies for evaluation of the speed of sound (and thus image quality improvement) have also been implemented in clinical ultrasound diagnostic equipment, and various applications have been reported. Hirooka has reported the clinical applications of this technology, since the early stages of its development [ 44 ]. Imbault has reported clinical data and proposed various methods for improving the accuracy of speed of sound evaluation technology [ 45 47 ].…”
Section: Speed Of Sound Evaluationmentioning
confidence: 99%
“…It is thus imperative to acquire adequate tissue specimens to improve the accuracy of histological examination [4]. As a new ultrasound technique, sound speed correction can quantitatively measure the tissue hardness [5], and it has been applied to differentiate between healthy and diseased tissues. We therefore used sound speed correction to guide performing EUS-FNA (▶ Video 1).…”
mentioning
confidence: 99%